2011
DOI: 10.1007/s12262-011-0255-0
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Angioedema-Presenting as Recurrent Abdominal Pain

Abstract: We report a very rare case of HEREDITARY ANGIOEDEMA, presenting as recurrent acute abdomen. A 22 yr old Maharastrian male, law college student, got admitted for about fifteen times in previous three years for severe, acute onset, upper abdominal pain, vomiting, distention and acute exudative inflammatory ascites .The whole episode used to subside spontaneously within 2-3 days with or without conservative general management .He underwent various investigations from far basic type, to advanced and invasive type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Recurrent abdominal pain may be seen in 30%‐100% of patients with HAE 27,31,52 . It may be the initial presenting symptom in 40%‐80% of children 16,53 . In the presented study, one‐third of all patients reported having gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Recurrent abdominal pain may be seen in 30%‐100% of patients with HAE 27,31,52 . It may be the initial presenting symptom in 40%‐80% of children 16,53 . In the presented study, one‐third of all patients reported having gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 49%
“…27,31,52 It may be the initial presenting symptom in 40%-80% of children. 16,53 In the presented study, one-third of all patients reported having gastrointestinal symptoms. Patients with predominant abdominal symptoms may inadvertently be subjected to exploratory laparotomy.…”
Section: Re Sultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The angioedema in HAE is not believed to be pruritic, while histaminergic angioedema often can be pruritic (42,52). Left untreated, angioedema in HAE often lasts for up to three to five days (47,53,54). There are also a few reports of patients with HAE having recurrent neurological symptoms that have been proposed to be due to cerebral swelling (2, 55).…”
Section: Clinical Manifestationsmentioning
confidence: 99%